Development of a chemiluminescence immunoassay for detection of tenuazonic acid mycotoxin in fruit juices with a specific camel polyclonal antibody. Issue 15 (24th March 2021) - Wang, Feng; Wan, De-Bin; Shen, Yu-Dong; Tian, Yuan-Xin; Xiao, Zhi-Li; Xu, Zhen-Lin; Yang, Jin-Yi; Sun, Yuan-Ming; Hammock, Bruce D.; Wang, Hong
Abstract : A rationally designed hapten with computer-assisted modeling was applied for generation of specific camel polyclonal antibody against TeA mycotoxin, and a sensitive chemiluminescence immunoassay was developed for TeA detection in fruit juices. Abstract : The natural mycotoxin tenuazonic acid (TeA) in foods is identified as the most toxic mycotoxin among the over 70 kinds of secondary toxic metabolites produced by Alternaria alternata . Some hapten–antibody-mediated immunoassays have been developed for TeA detection in food samples, but these methods show unsatisfactory sensitivity and specificity. In this study, a rationally designed hapten for TeA mycotoxin generated with computer-assisted modeling was prepared to produce a highly specific camel polyclonal antibody, and an indirect competitive chemiluminescence enzyme immunoassay (icCLEIA) was established with a limit of detection of 0.2 ng mL −1 under optimized conditions. The cross-reactivity results showed that several analogs and some common mycotoxins had negligible recognition by the anti-TeA polyclonal antibody. The average recoveries spiked in fruit juices were determined to be 92.7% with an acceptable coefficient of variation, and good correlations between icCLEIA and liquid chromatography tandem mass spectrometry (LC-MS/MS) results were obtained in spiked samples. This developed icCLEIA for TeA detection with significantly improved sensitivity and satisfactory specificity is a promising alternative for environmental monitoring and food safety.